Catholic converts : British and American intellectuals turn to Rome - Allitt, Patrick (Cornell University Press, 1997)
From the early nineteenth to the mid-twentieth century, an impressive group of English-speaking intellectuals converted to Catholicism. Outspoken and gifted, they intended to show the fallacies of religious skeptics and place Catholicism, once again, at the center of Western intellectual life. Allitt explains how, despite the Church's dogmatic style and hierarchical structure, converts working in the areas of history, science, literature, and philosophy maintained that Catholicism was intellectually liberating. British and American converts followed each other's progress closely, visiting each other and sending work back and forth across the Atlantic. The lives of individual converts - such as John Henry Newman, G.K. Chesterton, Thomas Merton, and Dorothy Day - have been well documented, but Patrick Allitt has written the first account of converts' collective impact on Catholic intellectual life.